Using The 5W1H Method In Writing Important Information With Google Forms In Elementary Schools - Lestari, Febrika; Herman, Tatang; Sujana, Atep (International Conference on Elementary Education, 2021)
This research is based on the lack of understanding of students in writing important information in the text. This research was aimed to determine the ability of primary school students in writing important information by using the method of 5W1H through the google form. The method used in this research is descriptive qualitative. The instrument used to measure the understanding of the students in writing important information is a test given through google form. Collecting data was given to 39 students of class 6 primary school. The sample was conducted by purposive sampling method. The Object of the research is grouped into four categories, they are understanding the whole, understanding the partial, misunderstanding, and not understanding. From the results of this research, it can be concluded that students can mostly understand partially, one-tenth of them cannot understand, and a fifth of them misunderstood, and only one-sixth of them understand the use of 5W1H in writing important information. Therefore, it is necessary to improve the quality of teaching and learning about the method of writing important information in a text at the primary school level.